MANAJEMEN PENDIDIKAN PONDOK PESANTREN DI KOTA METRO - Mujib, Abdul (JURNAL TAPIS, 2015)
An Islamic boarding school has a multidimensional role, namely: education, religious that preserve the values     of Islam, the development, awareness and strengthening civil society. Resolve social issues with a religious perspective. Make himself as educational institutions with quality community-based global / international. The boarding school can accelerate the development of human resources quality without losing the values     of spirituality. Constructing the quality of boarding school education is a necessity for people with three fundamental reasons: (1) education involving human figure is always dynamic, (2) Innovation of education due to the development of science and technology and (3) the demands of globalization which melts the boundaries of religion, culture even philosophy nation. Every organization, including boarding school has an activity-specific work activities in order to achieve the organization, one of the activities is the management. Despite gradual, in recent years, schools have instituted educational reformer perform various management field in response to the demands of global democratization. One form is democratic management model based culture, of, by and for learners. Educational boarding school is the center of conservation (preservation), deepening, development, refining, timeless values    and culture as well as the center of the implementation process of acculturation. If translated into Indonesian context, it may be filed relevant questions, such as whether the ideological aspects that successfully fought through politics, then managed to also be implemented through the managementKeywords: management, education, Islamic boarding school